TEKNIK PENGENDALIAN PENCEMARAN DARI PROSES PENCAIRAN BATUBARA - Soleh Soleh; Nevi Fatimah (Jurnal Energi dan Lingkungan (Enerlink), 2005)
Until now the reputation of fosil fuel, especially coal, indeed very bad if being connected with the problem of pollution of the environment. This happened because of the chemical chacarteristic of coal that had high aromatic level (fa) and particulate, heavy metals etc. However, the huge of coal reserved in Indonesia, especially low rank coal (lignite, triggered researches on the utilisation of these resources, in part through liquefaction technology of coal to produce synthetic fuel oil. Studied the potential for pollution of the process for the liquefaction of coal and its control technique, is one aspect to investigate in the commercialization coal liquefaction plant. The study of the environment towards the impact of pollution of the liquefaction process showed that pollution produced still under the threshold. Nevertheless when this technology was applied as commercial plant, the study of environmental impact is still needed.Kata kunci: Pengendalian pencemaran, pencairan batubara, teknik pengendalian